Bridging the Gap: Legal Perspective, Technology Limitation, Cultural Behavior into Solid Waste Management in Bekasi and Sumedang - Junerosano, Mohamad Bijaksana; Nurawaliah, Hanifah; Mordekhai, Jordan; Ni'am, Achmad Chusnun (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2024)
Indonesia faces increasing waste management challenges, driven by rapid urbanization, population growth, and inadequate infrastructure. This study examines the limitations of waste management technology in Bekasi City and Sumedang Regency by analyzing governance, legal frameworks, and cultural behavior. A mixed-method approach was employed, incorporating interviews, observations, and questionnaires with key stakeholders, supported by multiple linear regression analysis. The result reveals that governance is a significant factor, depicting the highest regression coefficient (B = 0.166). Weak regulatory enforcement and institutional inefficiencies are identified as primary barriers to effective waste management as governance issues. Additionally, cultural resistance to adopting new technologies significantly hampers the progress of waste processing systems. Comparative insights from other ASEAN countries, such as the Philippines, reveal similar governance-related obstacles. This study contributes to enriching the literature on the dynamics of waste management in Indonesia and providing objectivity in formulating policies. This study offers a unique perspective on policy formulation that combines law enforcement with cultural considerations to ensure the implementation of sustainable waste management technologies. The findings emphasize that technological solutions should be combined with governance reform and cultural alignment to effectively address the waste management crisis